Identifikasi Keragaman Gen Toll-Like Receptor-4 Ayam Lokal dengan Polymerase Chain Reaction- Restriction Fragment Lenght Polymorphism (THE GENETIC POLIMORPHISM OF TOLL-LIKE RECEPTOR-4 GENE IN LOCAL CHICKENS USING POLYMERASE CHAIN REACTION-RESTRICTION FRAG - Ulupi, Niken; ., Muladno; Sumantri, Cece; Wibawan, I Wayan Teguh (Jurnal Veteriner, 2014)
Toll-like Receptor 4 (TLR4) gene is one of the genes that control resistance of chickens againstSalmonella sp. through non-specific immune response. These gene can be used as genetic markers inIndonesian local chickens, if known its diversity. Therefore this research was aimed at evaluating thegenetic polymorphism of TLR4 gene in several types of Indonesian lokal chickens (kampung, kampungpelungcrossbreed, sentul, and tolaki chicken) using PCR-RFLP. The total of samples were 136. There werethree stages of identification : extraction of DNA genom, PCR amplification of TLR4 gene (with size 220 bpon exon 2), and RFLP method using restriction enzym (MscI). The data were analyzed include frequency ofallele, frequency of genotype, heterozygosity values , and value of Polymorphic Informative Content (PIC).The result showed that TLR4|MscI was found polymorphic in all kind of chickens that was genotyped. Itwere found two alleles (A and G), and three genotypes (AA, AG, and GG). The value of x2 showed thatTLR4|MscI was in Hardy-Weinberg equilibrium. The value of Ho and He were 0,11-0,41 and 0,11-0,35. Thevalue of PIC (0,10-0,29) included in the category of low to moderately high. These results declared thatTLR4|MscI gave hope for used as genetic markers in resistance to Salmonella sp. infection in Indonesianlocal chickens.
Keywords: genetic polimorphism, TLR4 gene, Salmonella sp., non-specific immune system